Influence of age on surgical treatment and postoperative outcomes of patients with colorectal cancer in Denmark and Yorkshire, England. (24th September 2021) - Taylor, John C.; Iversen, Lene H.; Burke, Dermot; Finan, Paul J.; Howell, Simon; Pedersen, Lars; Iles, Mark M.; Morris, Eva J. A.; Quirke, Philip; ,
Abstract: Aim: Denmark and Yorkshire are demographically similar and both have undergone changes in their management of colorectal cancer to improve outcomes. The differential provision of surgical treatment, especially in the older age groups, may contribute to the magnitude of improved survival rates. This study aimed to identify differences in the management of colorectal cancer surgery and postoperative outcomes according to patient age between Denmark and Yorkshire. Method: This was a retrospective population‐based study of colorectal cancer patients diagnosed in Denmark and Yorkshire between 2005 and 2016. Proportions of patients undergoing major surgical resection, postoperative mortality and relative survival were compared between Denmark and Yorkshire across several age groups (18–59, 60–69, 70–79 and ≥80 years) and over time. Results: The use of major surgical resection was higher in Denmark than in Yorkshire, especially for patients aged ≥80 years (70.5% versus 50.5% for colon cancer, 49.3% versus 38.1% for rectal cancer). Thirty‐day postoperative mortality for Danish patients aged ≥80 years was significantly higher than that for Yorkshire patients with colonic cancer [OR (95% CI) = 1.22 (1.07, 1.38)] but not for rectal cancer or for 1‐year postoperative mortality. Relative survival significantly increased in all patients aged ≥80 years except for Yorkshire patients with colonic cancer. Conclusion: This study suggests that there are major differences between the management of elderly patients with colorectal cancer between the two populations. Improved selection for surgery and better peri‐ and postoperative care in these patients appears to improve long‐term outcomes, but may come at the cost of a higher 30‐day mortality.